Efficacy of avilamycin for the prevention of necrotic enteritis caused by a pathogenic strain of Clostridium perfringens in broiler chickens. Issue 3 (3rd May 2016) - Paradis, Marie Anne; McMillan, Ewen; Bagg, Randal; Vessie, Gord; Zocche, Alexandre; Thompson, Michelle
ABSTRACT: The efficacy of avilamycin for the prevention of necrotic enteritis (NE) was investigated in a 35-day floor pen study of 2200 broiler cockerels using a Clostridium perfringens ( Cp ) feed inoculum challenge model. Treatments consisted of (1) nonmedicated, nonchallenged; (2) nonmedicated, challenged; (3) avilamycin at 15 ppm, challenged; (4) avilamycin at 30 ppm, challenged. Avilamycin was administered in the feed from day 7 to day 30 of the study. Challenge inoculum was administered on day 14 and delivered approximately 10 9 CFU Cp /bird. NE mortality rates from day 14–35 were significantly ( P < 0.0001) lower in birds treated with avilamycin at 15 and 30 ppm when compared to nonmedicated, challenged birds. Treatment with avilamycin also resulted in a significant reduction in ileal Cp count on day 21 ( P < 0.0001) and NE lesion scores on day 17 ( P < 0.006) when compared to nonmedicated, challenged birds. The performance of birds treated with avilamycin was also improved when compared to nonmedicated, challenged birds. Cockerels that received either 15 or 30 ppm avilamycin had a significantly ( P < 0.0001) increased body weight on day 35 and average daily gain from days 0–35 than nonmedicated, challenged birds. Furthermore, birds treated with avilamycin had an improved feed conversion rate from days 0–35 compared to both nonmedicated, nonchallenged birds and nonmedicated, challenged birds. This study confirms that avilamycin is effective at controlling mortality related to NE in growing broiler chickens.